Aplikasi Biodekomposer pada Media Tanam Anthurium (Anthurium andreanum): Application of Biodecomposer in Cultivation Media of Anthurium (Anthurium andreanum) - Ridho kurniati; Eka Fibrianty; Suryawati; Supenti; Sadli; Riska Syafrina (Jurnal Hortikultura Indonesia, 2024)
Decomposers have an important role in keeping an environment balance and land fertility. Applying microbes as a decomposer in plant cultivation media is also one solution to reduce chemical fertilizer to support sustainability in agriculture and be environmentally friendly. The research aimed to find the optimum bioagrodeco decomposer dose in cultivation media for anthurium clone propagation. Bioagrodeco is a biodecomposer in some levels (0, 5, 10, and 15 g), husk, charcoal husk, and cocopeat as material. Bioagrodeco consisted of Trichoderma koningii Kun4, T.harzianum Pan23.1, T.hamatum Gam4, T.viride Trv13, and Candida sp Y.BN. Anthurium PA (Anthurium cv. Putri Gunung x Angel) was used as plant material. The observation parameters were plant height, total number of shoots, total number of leaves, leaf length, and width. The optimum dose of Bioagrodeco was 5-10 g per medium for rice husk and rice husk charcoal. Bioagrodeco 5-10 g combined with rice husk and rice husk charcoal were recommended for anthurium propagation media. Both media showed anthurium propagation better than Bioagrodeco + cocopeat.Keywords: cocopeat, dose, microbe, rice husk, trichoderma